Hidden in Plain Sight: Natural Products of Commensal Microbiota as an Environmental Selection Pressure for the Rise of New Variants of SARS‐CoV‐2. (26th July 2021) - Dragelj, Jovan; Mroginski, Maria Andrea; Ebrahimi, Kourosh H.
Abstract: Since the emergence of SARS‐CoV‐2, little attention has been paid to the interplay between the interaction of virus and commensal microbiota. Here, we used molecular docking and dynamics simulations to study the interaction of some of the known metabolites and natural products (NPs) produced by commensal microbiota with the receptor binding domain (RBD) of the spike glycoprotein of SARS‐CoV‐2. The results predict that NPs of commensal microbiota such as bile acids and non‐ribosomal peptides (NRPs), of which some are siderophores, bind to the wild‐type RBD and interfere with its binding to the ACE2 receptor. N501Y mutation, which is present in many of the emerging variants of the virus, abolishes the predicted binding pocket of bile acids and NRPs. Based on these findings, available experimental data showing that bile acids reduce the binding affinity of wild‐type RBD to the ACE2 receptor, and the data suggesting that the respiratory tract microbiota affect viral infection we put forward the following proposal: mutations such as N501Y enable the RBD to bind to the ACE2 receptor more effectively in the presence of NPs produced by the respiratory tract bacteria thereby, increasing the infectivity rate of the virus. We hope our data stimulate future works to better understand the interactions of NPs produced by commensal microbiota with respiratory viruses like SARS‐CoV‐2. Abstract : In silico studies suggest that NPs like bile acids and non‐ribosomal peptides (NRPs) produced by bacteria residing in the respiratory tract can interfere with the binding of the original strain of SARS‐CoV‐2 to the ACE2 receptor but not with the binding of the emerging variants having the N501Y mutation. Thus, it is hypothesized that NPs of respiratory tract bacteria are an environmental selection pressure for the rise of new variants of the virus with higher infectivity rate.